Formation and transformation of mineral phases in various fuels studied by different ashing methods. (15th August 2017) - Reinmöller, Markus; Schreiner, Marcus; Guhl, Stefan; Neuroth, Markus; Meyer, Bernd
Highlights: Methods of plasma ashing at 200 °C and oven ashing at 450 and 815 °C are applied. Fuel ashes of a hard coal, a brown coal, a waste (RDF), and a biomass are studied. The ashing temperature has strongly influenced the composition of mineral phases. Deformation temperature is clearly reduced for ashes at 450 °C compared to 815 °C. All other ash fusion temperatures are less affected by the ashing temperature. Abstract: Ashes of four different fuels – comprising a hard coal, a brown coal, a refuse-derived fuel (RDF), and a biomass – are investigated in the present study. The ashes were generated by different methods of a plasma treatment with a low temperature of around 200 °C as well as in a classical ashing oven under respective medium and high temperatures of 450 and 815 °C. All ash compositions are analyzed by XRF. The mineral phases obtained by those three ashing methods are compared as well as their formation and transformation are illustrated as a function of temperature. These results are reproduced by thermochemical calculations using the software package FactSage™. Experimental and calculated mineral phases are in agreement. Subsequently, the ash fusion behavior is studied under oxidizing conditions. A solely reduction of the deformation temperature is detected for an ashing temperature of 450 °C compared to 815 °C. The determined flow temperatures can already be predicted by means of the composition of mineral phases in the ash produced at 815 °C under consideration of the melting point of those minerals. Finally, an influence of different ashing temperatures on the resulting ash fusion interval is ascertained for all investigated fuels.